Reinterpretation of the Meaning of Jihad within the Framework of National Jurisprudence - Pangestu, Pujo; Mubarok, Ahmad Ibnu (al-Rasῑkh: Jurnal Hukum Islam, 2025)
The misinterpretation of the concept of jihad in Islam has led to significant negative effects on both the Muslim community and the image of Islam globally. The term jihad is often mistakenly viewed solely as a holy war associated with violence, which has become the root cause of various conflicts between Muslims and other communities. This misunderstanding fails to capture the broader essence of jihad, which encompasses moral, spiritual, and social dimensions. This study aims to reinterpret the meaning of jihad within the framework of national jurisprudence, contextualizing the concept to align with modern challenges. The research method employed is library research, utilizing primary and secondary sources, including religious texts and scholarly articles. The findings indicate that jihad should be understood as efforts directed toward achieving progress and social justice, focusing on combating corruption, social injustice, and defending national sovereignty. Furthermore, jihad in the educational sphere aims to enhance the quality of education, fostering an informed society that contributes to national development. The contribution of this research is to provide a nuanced understanding of jihad that promotes peace and national unity, while countering radical interpretations.